Exploring changes in distress among individuals with bleeding disorders: What is linked to improvements in distress?. (October 2019) - Barry, Vaughn; Lynch, Mary Ellen; Tran, Duc Q; Antun, Ana; DeBalsi, Anthony; Hicks, Denise; Lasseter, Francie; Mattis, Shanna; Ribeiro, Maria JA; Stein, Sidney F; Kempton, Christine L
Adults with chronic bleeding disorders report high distress, but it is unclear how distress varies over time. Patients rated their distress on a 10-point scale at two clinic visits. Of 83 patients, roughly one-quarter reported consistent no/low distress (29%), one-quarter reported consistent distress (22%), and half (49%) reported a change in distress of at least two points. Overall activity levels, depressive symptoms, and non-White race were significantly associated with worsening and consistent distress in adjusted analyses while improvements in activity levels and depressive symptoms during the study period were associated with distress improvement. Our results suggest that distress is modifiable.